2001
DOI: 10.1074/jbc.m009409200
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Azido Fatty Acids Inhibit Phosphate Transport and Activate Fatty Acid Anion Uniport Mediated by the Mitochondrial Phosphate Carrier

Abstract: The electroneutral P i uptake via the phosphate carrier (PIC) in rat liver and heart mitochondria is inhibited by fatty acids (FAs), by 12-(4-azido-2-nitrophenylamino)dodecanoic acid (AzDA) and heptylbenzoic acid (ϳ1 M doses) and by lauric, palmitic, or 12-azidododecanoic acids (ϳ0.1 mM doses). In turn, reconstituted E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The resulting FA-induced H ϩ efflux increased with increasing initial amount of W303 yeast mitochondria. It is likely mediated by yeast carriers of the HTP flow-through, such as the ADP/ ATP carrier (48) or the phosphate carrier (39,49). In turn, the ATP insensitivity of H ϩ efflux with the reconstituted W303 extract and only slight (Ͻ10%) inhibition of FA-induced H ϩ efflux in UCP2 or UCP3 proteoliposomes by CAT agaric acid, 3 or methylenediphosphonate suggest that the ATP-sensitive H ϩ fluxes in UCP2 (UCP3) proteoliposomes are indeed due to UCP2 (UCP3) function, respectively.…”
Section: Fig 1 (A and B) Illustrates The Inhibition Of The Lauric Acmentioning
confidence: 99%
“…The resulting FA-induced H ϩ efflux increased with increasing initial amount of W303 yeast mitochondria. It is likely mediated by yeast carriers of the HTP flow-through, such as the ADP/ ATP carrier (48) or the phosphate carrier (39,49). In turn, the ATP insensitivity of H ϩ efflux with the reconstituted W303 extract and only slight (Ͻ10%) inhibition of FA-induced H ϩ efflux in UCP2 or UCP3 proteoliposomes by CAT agaric acid, 3 or methylenediphosphonate suggest that the ATP-sensitive H ϩ fluxes in UCP2 (UCP3) proteoliposomes are indeed due to UCP2 (UCP3) function, respectively.…”
Section: Fig 1 (A and B) Illustrates The Inhibition Of The Lauric Acmentioning
confidence: 99%
“…UCP1 is the UCP of brown and beige fat 15 - 18 , but the identity of UCP(s) responsible for I H in all other tissues has remained elusive. It was suggested that all ~50 members of the SLC25 superfamily of mitochondrial solute carriers can contribute to I H 19 , most notably the close UCP1 homologs UCP2 and UCP3 20 - 22 , AAC 7 - 9 , aspartate-glutamate carrier 8 , 23 , dicarboxylate carrier 8 , 24 , and phosphate carrier 25 , 26 . I H may also occur through the lipid phase without protein involvement 27 .…”
Section: Introductionmentioning
confidence: 99%
“…It is not known to be sensitive to other nucleotides. Other mitochondrial carriers, such as the glutamate [16] and phosphate carriers [17], will catalyse proton conductance in the presence of fatty acids. Specific UCPs (uncoupling proteins) also catalyse inducible proton conductance [1821].…”
Section: Introductionmentioning
confidence: 99%